Penerapan Lesson Studi Melalui Pelatihan Pola In-On-In dalam Meningkatkan Mutu Pembelajaran Pada Madrasah Ibtidaiyah - Durahman Durahman (EduBase : Journal of Basic Education, 2021)
Improving the quality of education can be started by improving the quality of teachers in teaching and professional behavior. Teacher upgrading and training is one form of the effort. The teacher coaching model to achieve the quality of learning in school is Lesson Study. Lesson Study is a "model of professional educator development through collaborative and sustainable learning learning based on the principles of collegality and mutual learning to build learning communities". The in-on-in training of lesson study implementation for madrasah ibtidaiyah teachers in the ministry of religion is an effort to improve the professionalism of madrasah teachers in managing learning. The training participants consisted of 30 madrasah ibtidaiyah teachers formed in 6 (six) groups according to grade level to carry out lesson study activities, among others: planning (plan), implement (do), and reflect (see). The final conclusion of the training participants increased their understanding of lesson study as an effort to improve the quality of learning. Abstrak Peningkatan mutu pendidikan dapat dimulai dengan meningkatkan mutu guru dalam mengajar dan berprilaku professional. Penataran dan pelatihan guru salah satu bentuk dari upaya tersebut. Model pembinaan guru untuk mencapai kualitas pembelajaran di sekolah adalah Lesson Study. Lesson Study adalah â€model pembinaan profesi pendidik melalui pengkajian pembelajaran secara kolaboratif dan berkelanjutan berlandaskan prinsip-prinsip kolegalitas dan mutual learning untuk membangun komunitas belajarâ€. Pelatihan in-on-in implementasi lesson study bagi guru madrasah ibtidaiyah di lingkungan kementerian agama adalah upaya meningkatkan profesionalitas guru madrasah dalam mengelola pembelajaran. Peserta pelatihan terdiri dari 30 orang guru madrasah ibtidaiyah dibentuk dalam 6 (enam) kelompok sesuai tingkatan kelas melaksanakan kegiatan lesson study antara lain : merencanakan (plan), melaksanakan (do), dan mereflekasi (see). Simpulan akhir peserta pelatihan meningkat pemahamannya terhadap lesson study sebagai upaya meningkatkan mutu pembelajaran.